Oral lichen planus with cutaneous manifestations: case report with emphasis on dental diagnostic criteria - Rodrigo R. Rodrigues; Juliana C. Pinheiro; Gabriel G. Silva; Carlos Augusto G. Barboza; Rafaella B. Leite
ABSTRACT Lichen planus is a chronic inflammatory disease involving the skin and mucosa, which often affects the oral cavity. The objective of this study is to report a case of oral lichen planus (OLP) with cutaneous manifestations and to discuss the clinical, histopathological aspects and the established treatment. A 61-years-old female white patient was referred for evaluation of white lesions in the oral mucosa. In the intraoral examination, multiple white lesions with striated appearance were observed in the jugal mucosa, tongue and border. The extraoral examination revealed scaly lesions on the arm, white spots on the legs, and nail dystrophy on feet. Based on biopsy of the oral lesions and the histopathological analysis, the diagnosis of OLP was confirmed. The patient underwent treatment with clobetasol propionate topical cream (0.5 mg), and was instructed to apply it to affected area, once or twice a day for four weeks. In the clinical follow-up after one month and 15 days, the improvement of the lesions could be analyzed. As OLP is a disease with an etiopathogenesis that is still poorly recognized, several factors may enable the development of this condition. Therefore, the dentist's clinical view is essential for the most effective treatment.